Hubungan Kelentukan Pergelangan Kaki Dan Power Otot Tungkai Terhadap Kemampuan Shooting Dalam Permainan Sepak Bola Pada Siswa Ektrakurikuler Sepak Bola SMAN 3 Selong Lombok Timur Tahun 2018 - Muhammad Akbar; Baiq Satrianingsih; Putra Muhammad Yusuf (Mandala, 2018)
Background of the research problem, there is lack of football achivement in the last few years in SMAN 3 Selong. Due to the bad strength and inappropriate accuracy in kicking. This study aims to determine the correlation of the ankle flexibility and limb muscle power toward shooting ability in football. Data collection and research are conducted by performance test, documentation and observation. In this study, data analysis using multiple correlation formula. The results showed that: 1) The correlation of X1 and Y obtained r-score < r table = 0.0011 < 0.468, it means Ha is rejected. 2) The correlation of X2 and Y obtained r score < r table = 0.0474 < 0.468, it means Ha is rejected. 3) The correlation of X1 and X2 obtained r score < r table = 0.002 < 0.468, it means Ha is rejected. So it can be concluded there is no correlation of the ankle flexibility and limb muscle power toward shooting ability in football on the football extracurricular students of SMAN 3 Selong East Lombok in 2018. There are three variables that is a closeness although the results of correlation coofesian got results R = 0.047 (Very Low).